A multi-analytical study of egyptian funerary artifacts from three portuguese museum collections - Schiavon, Nicola (2022)
A diachronic, multi-analytical approach combining EDXRF, µFTIR, µRaman, SEM-EDS, and Py-GC/MS has been adopted with the aim to study for the first time the painting materials used to decorate Egyptian funerary masks and sarcophagi ranging from the Late Period to the Roman Period and stored in the Archaeological National Museum (MNA) and the Carmo Archaeological Museum (MAC) of Lisbon and the Natural History Museum of the University in Oporto (MNH-FCUP). Results indicate that yellow and red ochres, realgar, cinnabar, Egyptian blue, and Egyptian green were used as pigments while chalk served as the preparatory layer. Over the 1000-year time-line of the studied artifacts, the palette remained remarkably consistent with previous findings as exemplified by cinnabar being used for red pigments in samples only dated after the Ptolemaic period. The presence of Sn in Egyptian blue and Egyptian green pigments used in one sample sug-gests the use of recycled bronze scraps during pigment production. Black pigments in two Late Period masks were found to be produced by mixing Egyptian blue with red ochre suggesting either a hitherto unknown method for production of purple pigments in the Egyptian palette or, alterna-tively, an attempt to create a specific hue or shade of dark brown or black. The results of this study contribute to further expand the database of Ancient Egyptian painting materials while at the same time helping to valorize three important Egyptian collections in Portugal.